Web-based 3D virtual environment for information visualization - Neo, Ker Sin (2008)
In this project, we proposed a web-based system that allows authors of electronic documents to create their own interactive 3D visualizations. Our proposed behavior definition model allows a content author to model behaviors of virtual objects by providing an interface for interacting with the 3D virtual environment. This improves the usability of the system as users with little or no programming and modeling experience will be able use it with little difficulty.